Evaluation of the reservoir architectural elements in deepwater turbidites of Niger Delta – a case study from the “AFUN” Field - AJISAFE, Yemisi C. (Contributions to Geophysics and Geodesy, 2021)
3D post-stack time migrated seismic data and a suite of composite well log data from six wells drilled within the “AFUN” field Niger delta were used to effect a detailed interpretation of the field. This was with a view to delineating architectural elements that control reservoir quality of a deepwater turbidite reservoir. The data analyses were done using the Petrel software. LAS file of logs were imported into the Petrel software as well as SEG.Y. seismic data. Fault interpretation and horizon mapping were based on the well-seismic tie from the generated seismogram. Time and depth structure maps were created. Thirty faults which include growth faults, reverse faults, collapsed crest structure and as well as faults that are synthetic and antithetic to the growth faults were mapped. The growth faults are believed to act as pathways for the updip movement of hydrocarbon from the Akata Formation to Agbada Formation. The structural interpretation showed that the area has been subjected to compressional deformation which resulted in reverse faulting system in toe thrust zone influenced by shale diapirs. The maps revealed contour closures that belong to an anticlinal structure which is forming traps in the reservoirs. The structures are faulted North-South trending rollover anticlines. It has also been shown that the distribution and type of architectural elements i.e. fractures within the fan system have major impact upon the reservoir distribution, continuity and connectivity of sand/shale bodies. The study concluded that structural style and facies architecture are the two fundamental elements that defined the reservoir heterogeneity of the “AFUN” Field.